The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/fwb.13645
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in Arctic freshwater chemistry—Reflecting climate‐induced landscape alterations and a changing template for biodiversity

Abstract: 1. Freshwater chemistry across the circumpolar region was characterised using a pan-Arctic data set from 1,032 lake and 482 river stations. Temporal trends were estimated for Early (1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), Middle (1986-2000), and Late (2001 periods. Spatial patterns were assessed using data collected since 2001.2. Alkalinity, pH, conductivity, sulfate, chloride, sodium, calcium, and magnesium (major ions) were generally higher in the nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 98 publications
(178 reference statements)
5
30
1
Order By: Relevance
“…In framing the UKRE, we initially anticipated that phosphorus delivery would increase with permafrost thaw (Bowden et al, 2008). In contrast, we observed a strong decrease in DOP flux (Figure 3) and decrease in TDP concentration (Kendrick et al, 2018) over time, consistent with a recent synthesis documenting pan‐Arctic decreases in total P in the Sub and Near Arctic (Huser et al, 2020). It is intriguing to connect decreasing P concentrations to widely documented permafrost thaw (e.g., Biskaborn et al, 2019; Box et al, 2019) and mobilization of iron from previously frozen soils (Herndon et al, 2017; Herndon et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In framing the UKRE, we initially anticipated that phosphorus delivery would increase with permafrost thaw (Bowden et al, 2008). In contrast, we observed a strong decrease in DOP flux (Figure 3) and decrease in TDP concentration (Kendrick et al, 2018) over time, consistent with a recent synthesis documenting pan‐Arctic decreases in total P in the Sub and Near Arctic (Huser et al, 2020). It is intriguing to connect decreasing P concentrations to widely documented permafrost thaw (e.g., Biskaborn et al, 2019; Box et al, 2019) and mobilization of iron from previously frozen soils (Herndon et al, 2017; Herndon et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Over the 37‐year period of seasonal monitoring in the UKRE, we have observed a significant decade‐by‐decade increase in nitrate flux during the fertilization period (Figure 3), consistent with changes in nitrate concentration reported from the Kuparuk River (Frey & McClelland, 2009 and sources therein; Kendrick et al, 2018) and trends in TN concentration observed in some – but not all – Arctic rivers (Huser et al, 2020). Given that discharge has not changed significantly during the period of record (Figure S1), we conclude that the more important driver of change in flux has been a change in concentration.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Besides temperature and spatial connectivity, water chemistry was also found to be an important diversity correlate, particularly for diatoms. Low diatom diversity in lakes in northern Quebec and Labrador in eastern Canada is likely to be a consequence of the historically stable cold temperatures in that region (Prowse et al, 2006) and the influence of the soft waters of lakes on the Precambrian Shield in this region (Huser et al, 2022;Kahlert et al, 2022).…”
Section: Potential Drivers Of α Diversitymentioning
confidence: 99%
“…The accelerated impacts of climate change at high latitudes [11,12] are a major threat to Arctic freshwater ecosystems [13], altering streamflow [14][15][16][17], warming [18,19] and drying [20] aquatic habitats; causing eutrophication [21] and browning of lakes [22,23]; and allowing for northward range expansion of eurythermic species [24]. To a lesser extent, long-range pollution [7], habitat loss and degradation, and flow modification from oil and gas development [25] can occur independently or interact with climatic change to alter Arctic freshwater ecosystems [26].…”
Section: Introductionmentioning
confidence: 99%